2003
DOI: 10.1067/mva.2003.40
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between aortic wall distensibility and rupture of infrarenal abdominal aortic aneurysm

Abstract: Women have a shorter time to AAA rupture. The measurement of AAA distensibility, diastolic BP, and diameter may provide a more accurate assessment of rupture risk than diameter alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
156
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 14 publications
3
156
2
4
Order By: Relevance
“…In 9 studies, AAA diameter was described as a marker for expansion8, 17, 19, 21, 40, 56, 57, 58, 59 and in 9 as a marker for rupture 34, 37, 60, 61, 62, 63, 64, 65, 66. Overall, the data are reliable because 2570 patients in total were included and 8 studies were appraised with low bias risk, 7 with medium risk, and only 3 with high risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 9 studies, AAA diameter was described as a marker for expansion8, 17, 19, 21, 40, 56, 57, 58, 59 and in 9 as a marker for rupture 34, 37, 60, 61, 62, 63, 64, 65, 66. Overall, the data are reliable because 2570 patients in total were included and 8 studies were appraised with low bias risk, 7 with medium risk, and only 3 with high risk.…”
Section: Resultsmentioning
confidence: 99%
“…In 6 studies, with a total of 552 patients, significant outcomes were demonstrated for AAA diameter as a marker for rupture. In 5 studies, larger diameters were measured in ruptured (and symptomatic) AAA when compared with asymptomatic patients,34, 60, 61, 64, 65 and 1 study demonstrated aneurysm diameter as a prognostic marker for rupture (area under curve=0.67) 37. In 3 studies, of which 2 were with high bias risk, no difference was found in diameter between ruptured AAA patients versus patients preceding elective repair (total n=80) 62, 63, 66…”
Section: Resultsmentioning
confidence: 99%
“…More recently this group has shown that the female gender, higher blood pressure, a decrease in the pressure strain elastic modulus (Ep), and a larger maximum diameter have a significant influence on time to AAA rupture. 32 Although the stiffness and compliance of AAAs can be investigated noninvasively using ultrasound techniques, this method cannot be used to derive the continuumbased constitutive models that are required when analyzing patient-specific local wall stresses on AAA using finite element analysis.…”
Section: In Vivo Mechanical Evaluationmentioning
confidence: 99%
“…8 Moreover, for a specific diameter, time until rupture is shorter in women than in men. 9 The underlying mechanisms of sex differences in the prevalence and incidence as well as the natural history of AAA are not fully understood. Here, we review human and animal studies summarized in Tables I, II, and III and discuss the different hypotheses proposed about the sex differences in AAA, regarding the role of sex hormones.…”
Section: Introductionmentioning
confidence: 99%